Understanding and Improving Web Search Using Large-Scale Observations and Experiments - Dumais, Susan (2014)
The rise of web-based services has made it possible to capture traces of human behavior in situ at a scale and fidelity previously unimaginable. This presentation will describe how large-scale observations and experiments enable us to characterize behavior and improve web search systems, with a focus on individual differences and temporal dynamics.
APS (Association for Psychological Science) Invited Session on Big Data